Mandatory reporting legislation in Canada: improving systems for patient safety?. Issue 3 (18th July 2021) - Milligan, C.; Allin, S.; Farr, M.; Farmanova, E.; Peckham, A.; Byrd, J.; Misfeldt, R.; Baker, G. R.; Marchildon, G. P.
Abstract: Patient safety is a complex systems issue. In this study, we used a scoping review of peer-reviewed literature and a case study of provincial and territorial legislation in Canada to explore the influence of mandatory reporting legislation on patient safety outcomes in hospital settings. We drew from a conceptual model that examines the components of mandatory reporting legislation that must be in place as a part of a systems governance approach to patient safety and used this model to frame our results. Our results suggest that mandatory reporting legislation across Canada is generally designed to gather information about – rather than respond to and prevent – patient safety incidents. Overall, we found limited evidence of impact of mandatory reporting legislation on patient safety outcomes. Although legislation is one lever among many to improve patient safety outcomes, there are nonetheless several considerations for patient safety legislation to assist in broader system improvement efforts in Canada and elsewhere. Legislative frameworks may be enhanced by strengthening learning systems, accountability mechanisms and patient safety culture.